Metachronous Multiple Primary Carcinoma With Acute Promyelocytic Leukemia: 2 Cases Report and Literature Review - Wang, Cong; Shen, Yamei; Zhang, Yuxia; Guo, Fahui; Li, Qian; Zhang, Huahua; Han, Xueping; Zhao, Haitao; Yang, Zilong (Frontiers in Oncology, 2022)
The co-occurrence of multiple primary cancers with hematological malignancies is uncommon, and acute promyelocytic leukemia (APL) with MPC is even rarer, with only a few cases reported in the literature. Herein, we introduce the diagnosis and treatment of 2 cases of MPC complicated with APL in our hospital and review the relevant literature. Both patients were primary solid tumor patients and were treated with surgery and chemotherapy, and had stable disease (SD). However, more than 1 year after the primary tumor was diagnosed, clinical symptoms were found and APL was diagnosed. Both patients received standard remission-induction therapy, but unfortunately died in the short term due to hemorrhagic complications. In conclusion, treatment of hematological neoplasms, especially acute leukemia combined with multiple primary cancers, is challenging. The prognostic factors and survival analysis of MPC patients with combined APL still need further clinical research and analysis.